HIV, food and drugs: Livelihoods, nutrition and Anti-retroviral Therap y (ART) in Kenya and Zambia - Samuels, Fiona; Rutenberg, Naomi (ODI, 2008)
Key points • ART has restored the health of many people living with HI V, but their livelihoods lag behind • Good nutrition is important for people on ART. Food supplementation can help, but is no substitute for sustainable livelihoods • The livelihoods of people on ART can be bol stered through skills, livelihood networks, assets and cash or food tr ansfers